Perancangan Buku Cerita Anak Kustomisasi yang Memiliki Nilai Personal Sebagai Hadiah dan Dapat Membantu Meningkatkan Kemampuan Literasi Anak - Cintia Natalia; Shienny Megawati Sutanto (Universitas Ciputra Surabaya, 2019)
This study aims to design customized children picture books that has personal value and can be gifted to children. The research method used is a mixed method of quantitative and qualitative. Primary data collection is done by observing competitors, interviewing and distributing online questionnaires to target markets, while secondary data collection uses literature studies. From this research, it is known that story books that are of interest to the market is one which contain educational content and has simple but interesting visual. Recommendations that can be given are to build brands and introduce products to wider market, as well as co-creation with parents and children who are the target market and users.